The Optical Properties Enhanced of Light-Emitting Polymer PFO: A Plasmon-Exciton Interaction Perspective (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The current experimental study presents the effect of silver nanoparticles (Ag NPs) on improving the optical properties of a light-emitting polymer (LEP) based on Plasmon-Exciton Coupling.Materials and Methods:A Poly(9,9-di-n-octylfluorenyl-2,7-diyl)(C29H41) polymer (PFO) is one of the light-emitting polymers that has distinctive optical properties when it is dissolved by toluene different concentrations.Further, the Ag NPs are experimentally synthesized by pulsed laser ablation in liquids technique to be subsequently mixed with the PFO polymer at different concentrations. Results:Based on the results, the Plasmon properties possessed by the Ag NPs improved the absorbance and fluorescence spectra of the PFO polymer for all concentrations. In addition, the light-induced fluorescence spectra are improved under the influence of laser beams by adding the Ag NPs to the PFO polymer.Conclusion: The current study showed that with increasing the concentration of the Ag NPs in the PFO polymer solution, a red shift appeared in the wavelength of the absorption and fluorescence spectra. This wavelength shift is most likely the result of the strong interaction between the plasmon of the Ag NPs and the exciton of the PFO polymer under the influence of laser light. In turn, this interaction can lead to changes in the energy states of the PFO polymer thus improving its optical properties.